Breaking Barriers; Socioeconomic Determinants of Household Consumption under the Leadership of Woman - Asrahmaulyana, Asrahmaulyana; Ma’ruf, Muhammad Imam; Qarina, Qarina; Aisyah, Sitti (EcceS: Economics, Social, and Development Studies, 2023)
Poverty in families led by women is a specific issue, with various limitations, including employment status that has the potential to influence consumption habits within the household in Makassar City. The novelty of this research is to provide a deeper understanding of the challenges, needs, and potential in seeking solutions to improve the economic conditions and well-being of single mothers, especially in the specific local context of Makassar city. The expected future impact of this research is that stakeholders can collaborate to create positive changes in the lives of single mothers. The research adopts a quantitative approach with a path analysis method, using primary data, namely direct research or direct observation of the research subjects to obtain relevant information.The results show that the direct relationship between education and employment type has a positive and significant impact on women's income in Makassar City, while age and the number of family members have a negative and insignificant effect on women's income in Makassar City. Additionally, it was found that the education variable has a negative and insignificant impact on household consumption in Makassar City; conversely, age, the number of family members, employment type, and women's income have a positive and insignificant effect on household consumption in Makassar City. The indirect relationships based on the research results indicate that the education variable has a negative and significant impact on household consumption through women's income, while age, the number of family members, and employment type have a positive and significant impact on household consumption through women's income. Thus, the overall study provides an overview that factors such as education, employment type, age, the number of family members, and women's income play different roles in influencing income and household consumption in Makassar City. Policy implications of these findings may include efforts to enhance access to education and employment opportunities for women to increase household income and consumption.